Increased expression of hepatocyte nuclear factor 4 alpha transcribed by promoter 2 indicates a poor prognosis in hepatocellular carcinoma. (October 2017) - Cai, Shao-hang; Lu, Shi-xun; Liu, Li-li; Zhang, Chris Zhiyi; Yun, Jing-ping
Background: Hepatocyte nuclear factor 4 alpha (HNF4α) plays an important role in tumourigenesis. There is growing evidence indicating that HNF4α transcribed by promoter 1 (P1-HNF4α) is expressed at relatively low levels in HCC and its presence predicts a favourable outcome for hepatocellular carcinoma (HCC) patients. However, the role of HNF4α transcribed by promoter 2 (P2-HNF4α) in HCC remains unclear. Methods: A total of 615 HCC specimens were obtained to construct tissue microarrays and perform immunohistochemistry. The relationship between P2-HNF4α and clinical features of HCC patients were analysed. Kaplan–Meier analysis was conducted to assess the prognostic value of P2-HNF4α. Results: The results showed that the expression of P2-HNF4α in HCC was noticeably increased in HCC tissues compared with the nontumourous tissues. In addition, P1-HNF4α expression was negatively correlated with P2-HNF4α expression ( p = 0.023). High P2-HNF4α expression was significantly associated with poor differentiation of HCC ( p = 0.002) and vascular invasion ( p = 0.017). Kaplan–Meier analysis showed that P2-HNF4α expression was closely correlated with overall survival in the training group ( p = 0.01), validation group ( p = 0.034), and overall group of patients with HCC ( p < 0.001). Conclusions: Our data show that the role of HNF4α in cancer development needs to be further refined. P2-HNF4α, different from P1-HNF4α, is markedly upregulated and serves as an oncogene-associated protein in HCC. Our study therefore provides a promising biomarker for prognostic prediction and a potential therapeutic target for HCC.